PTU-023 The use of argon plasma coagulation to prevent colorectal polyp recurrence following piecemeal endoscopic mucosal resection. (22nd June 2015) - Chattree, A; Rutter, MD
Abstract : Introduction: High levels of recurrence and residual tissue have been reported following piecemeal endoscopic resection (pEMR) of large colorectal polyps with figures approaching 30% described. 1 The application of argon plasma coagulation (APC) has been advocated to reduce recurrence following pEMR, with early data appearing to support the use of APC to treat tiny polyp fragments not amenable to endoscopic snare resection. 2 More recent data however, appears to oppose this view, suggesting no change in or even increased recurrence following adjunctive APC use. 1 With a lack of standardised APC application in relevant international case series, many of which include only small sample sizes, the position regarding its benefit remains controversial. Method: Retrospective analysis was conducted on 153 pEMR procedures undertaken in the Bowel Cancer Screening Programme (BCSP) between 2011–12. Recurrence rates on first endoscopic follow-up were compared between 2 groups (APC use vs no APC use). Statistical analysis was performed using the chi-squared test. Results: Recurrence was detected on first endoscopic follow-up in 25.5% of cases. A lower level of recurrence was seen in the APC group compared with the non APC group (17.9% vs 31.4%), with statistical significance seen on 1-sided but not 2-sided chi square analysis (p = 0.042 (1-sided), p = 0.064 (2-sided)) Conclusion: While statistical significance was only seen on 1-sided chi-square analysis, the level of recurrence was over 40% lower in the APC group (17.9% vs 31.4%). It can be argued that our study may be underpowered and that the result indicates likely clinical significance. Our data does not support the data from other studies indicating a possible detrimental effect of APC. Whilst the use of APC is likely to be more standardised within the BCSP, the exact circumstances of its use, such as the amount of residual tissue post snare resection remaining prior to APC use in other studies, is unclear. We believe APC is appropriate therapy for tiny residual polyp fragments post snare resection, but should not be used on larger tissue areas. A large randomised controlled trial with a standardised protocol for APC application would add further evidence. Disclosure of interest: None Declared. References: Moss A, Bourke MJ, Williams SJ, et al . Endoscopic mucosal resection outcomes and prediction of submucosal cancer from advanced colonic mucosal neoplasia. Gastroenterology 2011;140:1909–18 Brooker JC, Saunders BP, Shah SG, et al . Treatment with argon plasma coagulation reduces recurrence after piecemeal resection of large sessile colonic polyps: a randomized trial and recommendations. Gastrointest Endosc. 2002;55:371–5